Historický přehled Psychometrických přístupů ke zjišťování maskuliny/feminity a struktura maskulinních a feminních osobnostních rysů v České republice - Trnka, Radek (Lidé města, 2006)
A brief overview of psychometric instruments for measuring of masculinity and femininity is provided in this paper. Limitations of such measurement are discussed as well. The preliminary results of “Personal Attributes Questionnaire” – PAQ (Spence, Helmreich a Stapp, 1974; Spence a Helmreich, 1978) are presented in the next part of the study. This assessment was made on 201 Czech university students (f=101; m=100). The preliminary results suggest that examined population sample consists of 20% feminine, 19% masculine, 23% androgynous and 38% undifferentiated persons.